Penerapan Sistem Informasi Manajemen Sebagai Sarana Membangun Mutu Pendidikan - Sutarto; Ine Heidiani Ikasari (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Education is one of the vital sectors in national development. To enhance the quality of education, the role of management information systems has been recognized as an effective means. This research aims to analyze the implementation of management information systems in improving the quality of education. Three previous journals have been used as references to gather information on the implementation of management information systems in the educational environment. The research methodology employed is an analysis of these journals. The results of this research indicate that the implementation of management information systems in education still faces challenges and obstacles. However, overall, the implementation of management information systems in schools has provided a positive contribution to improving the quality of education.